Logics for “Non-Logical” Argumentation: A “Neo-Logicist” Defense of the Primacy of the “Logical” Mode of Argument in Gilbert’s Multi-modal Theory of Argumentation - Godden, David (Informal Logic)

(untitled) (Informal Logic, 2022)
On Gilbert’s multi-modal theory of argumentation, the “logical” is but one among many modes of argument, including the emotional, the visceral (physical), and the kisceral (intuitive). Yet, I argue that, properly understood, the logical is not one mode among many. Rather, it is better understood as the uber-mode of argument. What Gilbert calls the “logical mode” of argument—a linear, orderly, highly verbalizable, way of arguing—is made possible only to the extent that the logic of some space of reasons has been articulated. The “anti-logical” penchant of multi-modal argumentation is not found at the object-level—in its countenancing “non-logical” modes of argument, but at the meta-level—in its resistance, as a mistaken embracing of the “logical” mode, to using the logics governing the different modes to self-regulate the course of our arguings.